Social Enterprises in Poland During the War in Ukraine (Economic and Political Thought, 2023)
The research problem undertaken by the author is the activity of social enterprises, which, despite the negative impact of the war in Ukraine, have a positive impact on minimizing the effects of the refugee crisis. The aim of the article is to verify the hypothesis that a social enterprise situated in the order of a social market economy can mitigate the effects of the crisis by taking additional measures for refugees in connection with the war in Ukraine. The premise for undertaking the research topic is the research gap in the literature in the field of combining these two pro-social concepts and assessing how a social enterprise can fill the bottom-up gaps resulting from the weakness of the order of the social market economy in Poland. To verify the hypothesis, the author used a study for the purposes of the doctoral dissertation carried out from April 2, 2023 to July 31, 2023. The subject of the study was 378 entities from the database of 2,180 social enterprises. The key conclusion of the study is that social enterprises affected by the war in Ukraine are also able to minimize its effects by helping refugees.
Keywords: war in Ukraine, refugee crisis, social enterprise, economic order, social market economy